The short story of Sang Pemimpin as a means of conflict resolution - Amalia, Triana; Sapriya, Sapriya; Effendi, Ridwan (Universitas Negeri Yogyakarta, 2024)
Conflict is unavoidable, especially for Generation Z who are currently studying at the junior high school level. They are always familiar with the internet and social media and tend to avoid conflicts with family, friends or in the surrounding environment. Researchers focus on Conflict resolution skills included in the dimensions of social participation skills in social studies learning. This research aims to determine how effective the short story media